SINGLE-CRYSTAL XRD, TEM, AND THERMAL STUDIES OF THE SATELLITE REFLECTIONS IN NEPHELINE - Hassan I.; Antao S.M.; Hersi A.A.M. (My University, 2003)
A sample of nepheline from Egan Chute, near Bancroft, Ontario, with a chemical composition (K1.332□ 0.68) (Na6.05Ca0.22) [Al7.77Si8.21O32], has been studied using single-crystal X-ray diffraction, transmission electron microscopy (TEM), thermal analyses, and powder X-ray diffraction. Its structure was refined in space group P63 to an R1 index of 0.041 on the basis of 737 unique observed reflections. The parameters of the pseudohexagonal subcell are a 9.9853(7), c 8.3689(17) Å. The Al and Si atoms are fully ordered. The O1 framework oxygen atom is disordered over three nearby positions that are slightly displaced off the threefold axis in the average structure. Vacancies are present at the K site. Selected-area electron diffraction (SAED) patterns show that the satellite reflections are very weak and diffuse, and give rise to an incommensurate supercell. Images obtained by high resolution transmission electron microscopy (HRTEM) indicate that nepheline probably consists of domains that are separated by possible antiphase boundaries (APBs). Results from thermal analyses indicate that a displacive transformation occurs in nepheline at 292°C and represents a positional order-disorder of OI oxygen atoms. A K - □ order-disorder transformation occurs at 399°C and is attributed to disordering of K ions and □ vacancies in the large sixfold channels of the nepheline structure. An A1-Si order-disorder transformation occurs at 963°C and involves the highest energy among the various transitions. The ordering that gives rise to the satellite reflections is destroyed in the electron beam and results in twinned unit-cells.
Keywords: nepheline; crystal structure; superstructure; single-crystal X-ray diffraction; transmission electron microscopy; thermal analyses; phase transitions; Egan Chute; Bancroft; Ontario